The Effect of Using Instagram Assisted Vlogging on EFL Students’ Speaking Ability - Ananda Nasution, Tasha Bella; Risnawati; Anita (Yayasan Darussalam Bengkulu, 2022)
The purpose of this study was to to find out the significant effect of using Instagram assisted vlogging which was focused on speaking. The research design in this research was quasi experimental research. The instrument to collect the data was test by oral test. The strategy taken sample used is purposive sampling to determine the control and the experimental class. In addition, there were pre-test, treatment or teaching and post-test in both of the class. It was conducted at the twelfth grade of MAN 1 Kota Bengkulu. The result showed that are average value of pre-test in the control class was 36,80, while the experimental class was 42,40. Then the average value of the post-test control class 44,00, while the experimental class is 60,27. Based on the result hypothesis testing shows that the value of Sig. (2 tailed) obtained is 0.49 (0.49 > 0.05). This is indicated that Ho is rejected and Ha is accepted. It can be concluded that there is a significant effect on the using Instagram assisted Vlogging in improving students’ speaking ability.